Perancangan Dan Pembuatan Website Bloger Pada UMKM Bengke Paruik - Adinda Vania; M.Harif Ramadhan; Novita Ramadhani; Novadilastri; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The rapid development of digital technology has had a significant impact on various aspects of life, including how to do business. One trend that is becoming increasingly prominent is the digitalization of small and medium enterprises (MSMEs), especially in the marketing sector. Among various digital tools, blogs are one medium that has great potential in supporting digital marketing strategies. Blogs allow companies to present in-depth information, build brand image, and attract consumer attention through relevant and useful content. Food MSMEs, one of the sectors that continues to grow in Indonesia, require the right marketing strategy to compete in an increasingly competitive market. One of the MSMEs that has great potential is "Bengke Paruik", which operates in the field of traditional regional culinary specialties. This website not only functions as an online storefront, but also as a medium for sharing information about the products presented. Thus, it is hoped that the blog can become a communication bridge between "Bengke Paruik" and consumers, while increasing customer awareness and loyalty